2016
DOI: 10.1111/dme.13090
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient diabetes clinical decision support: current status and future directions

Abstract: Outpatient clinical decision support systems have had an inconsistent impact on key aspects of diabetes care. A principal barrier to success has been low use rates in many settings. Here, we identify key aspects of clinical decision support system design, content and implementation that are related to sustained high use rates and positive impacts on glucose, blood pressure and lipid management. Current diabetes clinical decision support systems may be improved by prioritizing care recommendations, improving co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 64 publications
1
51
0
3
Order By: Relevance
“…Prototype EHR-linked, Web-based clinical decision support systems that identify and prioritize clinical options, however, save time, satisfy clinicians, empower patients, have high use rates, and improve care are now up and running in several large health care systems. 15,16 Web services that include risk prediction equations can receive patient-specific data that are automatically sent from an EHR, perform the multiple computations needed to estimate the relative benefits of alternative treatment options, and display patientspecific prioritized treatment options on the EHR screen within 1 second.…”
Section: How To Apply Prioritization In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Prototype EHR-linked, Web-based clinical decision support systems that identify and prioritize clinical options, however, save time, satisfy clinicians, empower patients, have high use rates, and improve care are now up and running in several large health care systems. 15,16 Web services that include risk prediction equations can receive patient-specific data that are automatically sent from an EHR, perform the multiple computations needed to estimate the relative benefits of alternative treatment options, and display patientspecific prioritized treatment options on the EHR screen within 1 second.…”
Section: How To Apply Prioritization In Practicementioning
confidence: 99%
“…The potential benefits associated with better blood pressure management, cholesterol management, smoking cessation, or other clinical options can then be similarly estimated and then prioritized based on potential clinical benefit. 15,16 This approach to prioritization has a number of important limitations. Risk estimates are necessarily derived from groups of people and thus cannot precisely predict future risk for one person.…”
mentioning
confidence: 99%
“…In another work focusing on different domains, recent evidence has shown that, despite sometimes ineffective outcomes that can result in part from low use of CDS functionality, use of CDS to provide diabetes care can be improved by prioritizing care recommendations, improving communication of treatment-relevant information to patients, using such systems for care coordination and case management, and integrating patient-reported information and data from remote devices [48]. In other settings, CDS continues to hold promise for improving public health through disease surveillance and helping to intervene against outbreaks, including recent work to model spread of the Zika virus in dynamic human and vector populations [49].…”
Section: Expansion Of Clinical Settingsmentioning
confidence: 99%
“…In fact, it is recommended that decision support be provided in EMR to facilitate easy referral (24). DSME and MNT are crucial components of high-quality diabetes care (9,13).…”
Section: Dsme Referral: When and Whatmentioning
confidence: 99%